Preliminary study of probiotics and kynurenine pathway in autism spectrum disorder - Waranan Tharawadeephimuk (2020)
© 2019 IEEE. Autism spectrum disorder is a neurodevelopment syndrome. Nowadays, it can't be completely cured. From 'GutBrain-Axis' theory says that probiotics can help neurological disease such as autism. It can change the microorganism in the digestive tract to be equilibrium so the autism symptom is improve. The aims of this study are to find the effect of oral probiotics to brain inflammation via kynurenine pathway and autism symptoms. Ten autistic children were included in this study. All participants received probiotics in form of powder with three strains (Lactobacillus rhamnosus, Lactobacillus paracasei and Bifibidobacterium longum). Probiotics were given once daily for 6 weeks. Autistic symptoms were assessed by Autism Treatment Evaluation Checklist (ATEC) at 0 and 6 weeks. After probiotics supplement, the mean total ATEC scores were significantly decreased from 65.2 ± 30.66 to 50.5 ± 19.44( p-value= 0.041). Four domains of ATEC score were also decrease after probiotics supplement (speech / language / communication, sociability, sensory / cognitive awareness and health / physical / behavior). The effect of probiotics on brain inflammation via kynurenine pathway in children with autism spectrum disorder is still needed for further study.